Permanent campaign in Poland – causes, elements, importance - Zaręba, Agnieszka (Political Preferences, 2016)
A permanent campaign is one of the elements of political communication. It can be observed as a process since at least 2004. It results not only from the high media saturation of society, but also the instruments used during the campaign and the ways of managing it. The aim of this analysis is the description of the phenomenon of the permanent campaign in Poland in terms of its genesis, elements and importance. The permanent campaign in Poland depends on several factors. First of all, its existence is possible thanks to the development of new media, political advising, and media visibility of politician’s activity. The permanent campaign has lasted in Poland since 2004. It is connected with the development of political consulting and the appearance for the first time in Poland of specific media performances, such as inquiry committees. They were a kind of media attraction for viewers. An important element of the permanent campaign is the functioning of a multi-dimensional conflict between the rulers and the opposition. Antagonism is usually based on a different system of values, is difficult to eliminate, is profitable for both sides of the conflict, because it arouses the interest of the media and the audience’s attention. Key words: permanent campaign, political campaign, political communication